2021
DOI: 10.1186/s43055-021-00418-z
|View full text |Cite
|
Sign up to set email alerts
|

Three steps approach for preoperative evaluation of tetralogy of Fallot patients: role of 128 MDCT

Abstract: Background Tetralogy of Fallot is the most common congenital cyanotic heart disease. Advances in surgical repair recently facilitate survival of the affected patients into adulthood with good quality of life. Despite imaging plays crucial role in diagnosis of TOF patients, no single diagnostic modality suffices for complete evaluation of TOF. Thus, different diagnostic tools should be used alone or in combination according to patient’s clinical question. This study aims to find out the agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…Apart from the normal branching pattern, the most common left-sided aortic arch pattern was the bovine arch, including the common origin of the innominate artery and the LCC, which were seen in 40.95% and 16.19% of patients, respectively. These findings are in accordance with those of Moustafa et al (40.4% and 22.8%) [ 29 ] and Tawfik et al (36% and 16%) [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Apart from the normal branching pattern, the most common left-sided aortic arch pattern was the bovine arch, including the common origin of the innominate artery and the LCC, which were seen in 40.95% and 16.19% of patients, respectively. These findings are in accordance with those of Moustafa et al (40.4% and 22.8%) [ 29 ] and Tawfik et al (36% and 16%) [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the Popieluszko classification, the most frequently seen anomalous arch pattern in our patients was the RAA variant (23.8%). The incidence of RAA has been reported as around 25% in previous studies [ 7 , 18 , 29 ]. Apart from the normal branching pattern, the most common left-sided aortic arch pattern was the bovine arch, including the common origin of the innominate artery and the LCC, which were seen in 40.95% and 16.19% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…MPA stenosis/obstruction was observed in 19 individuals, which accounts for 63.3% of the patients, followed by LPA stenosis in 14 patients (46.7%), and RPA stenosis in 10 patients (33.3%). These findings align with the results reported by Moustafa et al [12] and Zakaria et al [10], who stated that the most prevalent pulmonary artery abnormality was combined MPA stenosis and its branches with 17 % incidence. This contrasts with the findings of Sheikh et al [16], the most frequent anomaly reported by 10% of their patients was isolated left pulmonary stenosis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, MDCT detected the four classic TOF symptoms in 100 percent of cases which corresponds with Shehata et al [11] and Moustafa et al [12] in their research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation